Salmonella Contamination in a Poultry-Processing Plant - Morris, George K. (1970)
Bacteriological examination of 1,427 samples from a poultry-processing plant over a 2-year period yielded 202 (14.2%) cultures positive for salmonellae. The results indicate that contamination is reduced by washing procedures within the plant but that recontamination of the carcasses occurred in at least two different stages of processing, i.e., during evisceration and chilling. There was evidence of spread of salmonellae from flock to flock during the serial processing of flocks, but the spread was usually not extensive. The serotypes of salmonellae isolated in this study were similar to those of chicken origin reported from other areas of the country.